ChemInform Abstract: Copper‐Assisted Nickel Catalyzed Ligand‐Free C(sp2)—O Cross‐Coupling of Vinyl Halides and Phenols. Issue 31 (5th August 2014) - Kundu, Debasish; Maity, Pintu; Ranu, Brindaban C.
Abstract A library of aryl‐vinyl and aryl‐styrenyl ethers is prepared.